Pelatihan Bahasa Inggris Komunikatif Melalui Program English Day pada Madrasah Aliyah - Moh. Arif Mahbub; Dyah Ayu Nugraheni; Suhaimah Bulqiyah; Devi Nur Indah Sari (IKIP PGRI Bojonegoro, 2021)
ABSTRACTTo get fluent in English is certainly a dream for many individuals to compete in today’s workplace. However, the empirical data from several previous studies show that the ability to speak English has become a serious problem for most of English Language Learners (ELLs). This phenomena have also emerged in one of a private Madrasah Aliyah (Islamic Senior High School) in Jember, Indonesia. Therefore, it is highly necessary to execute the English Day Program to facilitate them to develop their English speaking proficiency. This community service program is carried out for approximately more than three months from August – October 2018 which is consisted of eight meetings and several weeks for program evaluation. This community service program has received a big welcome from both participants and that institution. The majority of participants were largely enthusiastic participating in this program. Conclusion and recommendations are then discussed at the last part of this report.Keywords: Communicative English Language, Effective Communication, English Day Program. ABSTRAKMenjadi seseorang yang mahir berbahasa inggris tentunya menjadi impian bagi banyak kalangan untuk menjawab tuntutan berkompetisi di tempat kerja. Namun, data empiris dari beberapa riset terdahulu menunjukkan bahwa kemampuan untuk berbahasa inggris menjadi permasalahan yang serius untuk kebanyakan pelajar Bahasa Inggris (ELLs). Fenomena ini juga telah dialami di salah satu Madrasah Aliyah Swasta di Jember, Indonesia. Oleh karena itu, sangat perlu untuk melaksanakan Program Hari Bahasa Inggris untuk memfasilitasi mereka dalam mengembangkan kemampuan berbahasa Inggris mereka. Program ini dilaksanakan selama kurang lebih tiga bulan antara bulan Agustus – Oktober 2018 yang terdiri atas delapan kali pertemuan dan beberapa minggu untuk evaluasi. Program English Day ini mendapatkan sambutan yang sangat positif baik dari peserta maupun pihak sekolah. Sebagian besar peserta sangat antusias berpartisipasi dalam kegiatan ini. Simpulan dan rekomendasi juga didiskusikan pada akhir laporan ini